Analysis of the Effect of Efficiency on Bankruptcy at the Rural Bank in Surabaya - Kristiyanto, Sony; Haryanto, Tri; Kusumawardani, Deni (Jurnal Samudra Ekonomi dan Bisnis, 2025)
Unlike commercial banks, rural banks have their own uniqueness that they only provide basic banking services. It is important because, they serve more people with low financial literacy. This condition requires rural banks in a healthy condition to be able to serve the financial transaction needs of the community. This research attempts to see how efficiency relates to the potential for bankruptcy in rural banks. By using the Springate score to see the potential for bankruptcy and the DEA to calculate efficiency, this research concludes that the level of efficiency has no effect on the potential for bankruptcy in rural banks. While other variables in this research, namely total liabilities, total assets, operating costs and operating income have a significant effect on the potential for bankruptcy in rural banks.